CCL2 induces resistance to the antiproliferative effect of cabazitaxel in prostate cancer cells. Issue 1 (7th December 2018) - Natsagdorj, Ariunbold; Izumi, Kouji; Hiratsuka, Kaoru; Machioka, Kazuaki; Iwamoto, Hiroaki; Naito, Renato; Makino, Tomoyuki; Kadomoto, Suguru; Shigehara, Kazuyoshi; Kadono, Yoshifumi; Lin, Wen‐Jye; Maolake, Aerken; et al.
Abstract : Understanding the mechanism of chemoresistance and disease progression in patients with prostate cancer is important for developing novel treatment strategies. In particular, developing resistance to cabazitaxel is a major challenge in patients with docetaxel‐resistant and castration‐resistant prostate cancer (CRPC) because cabazitaxel is often administered as a last resort. However, the mechanism by which cabazitaxel resistance develops is still unclear. C‐C motif chemokine ligands (CCL) were shown to contribute to the castration resistance of prostate cancer cells via an autocrine mechanism. Therefore, we focused on CCL as key factors of chemoresistance in prostate cancer cells. We previously established a cabazitaxel‐resistant cell line, DU145‐TxR/CxR, from a previously established paclitaxel‐resistant cell line, DU145‐TxR. cDNA microarray analysis revealed that the expression of CCL2 was upregulated in both DU145‐TxR and DU145‐TxR/CxR cells compared with DU145 cells. The secreted CCL2 protein level in DU145‐TxR and DU145‐TxR/CxR cells was also higher than in parental DU145 cells. The stimulation of DU145 cells with CCL2 increased the proliferation rate under treatments with cabazitaxel, and a CCR2 (a specific receptor of CCL2) antagonist suppressed the proliferation of DU145‐TxR and DU145‐TxR/CxR cells under treatments of cabazitaxel. The CCL2‐CCR2 axis decreased apoptosis through the inhibition of caspase‐3 and poly(ADP‐ribose) polymerase (PARP). CCL2 is apparently a key contributor to cabazitaxel resistance in prostate cancer cells. Inhibition of the CCL2‐CCR2 axis may be a potential therapeutic strategy against chemoresistant CRPC in combination with cabazitaxel. Abstract : Cabazitaxel‐resistant cell line DU145‐TxR/CxR cells secreted CCL2, and CCL2 induces resistance to the antiproliferative effect of cabazitaxel in DU145‐TxR/CxR cells in an autocrine manner. Inhibition of the CCL2‐CCR2 axis may be a potential treatment candidate in combination with cabazitaxel.